2014
DOI: 10.4314/ijest.v6i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of surface roughness in turning of GFRP composites using genetic algorithm

Abstract: Glass fiber reinforced polymer composites are finding its increased applications in variety of engineering applications such as aerospace, automobile, electronics and other industries. However, the users of FRP are facing difficulties to machine it, because of fiber delamination, fiber pull out, short tool life, matrix debonding and formation of powder like chips. The present investigation focuses on the optimization of process parameters for surface roughness of glass fiber reinforced polymer (GFRP) composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, Kumar Parida et al [27] stated that optimum cutting parameters for better surface quality were obtained from low feed rate, cutting speed, and depth of cut, and they stated that the most effective parameter was cutting speed. In a study conducted by Hussain et al [28], surface roughness value increased with increasing fiber orientation angle and feed rate, and it decreased with increasing cutting speed and depth of cut. According to Gupta and Kumar [29], in turning of GFRP composites, surface roughness value decreased with increasing tool nose radius.…”
Section: Introductionmentioning
confidence: 95%
“…However, Kumar Parida et al [27] stated that optimum cutting parameters for better surface quality were obtained from low feed rate, cutting speed, and depth of cut, and they stated that the most effective parameter was cutting speed. In a study conducted by Hussain et al [28], surface roughness value increased with increasing fiber orientation angle and feed rate, and it decreased with increasing cutting speed and depth of cut. According to Gupta and Kumar [29], in turning of GFRP composites, surface roughness value decreased with increasing tool nose radius.…”
Section: Introductionmentioning
confidence: 95%
“…Experiments were carried out with different machining parameters like cutting speed, feed rate, depth of cut and cutting environment (dry and wet) and these machining parameters were optimized by using feed forward back propagation Artificial Neural Network (ANN) method. Hussain et al [30] applied the Genetic Algorithm (GA) for the optimization of machining variables viz. cutting speed, feed, depth of cut, and work piece (fiber orientation angle) for surface roughness in turning of GFRP composites with poly-crystalline diamond (PCD) tool.…”
Section: State Of Art: Turning Of Gfrp Compositesmentioning
confidence: 99%
“…Taguchi method combination with fuzzy logic resulted in low cutting force, surface roughness, cutting power, and specific cutting pressure in machining GFRP composites using carbide K20 cutting tool. Surface methodology and genetic algorithm were also used by Hussain et al [16] to optimise parameters during turning of GFRP. It was observed that the quality of the surface improved when response surface method was used in combination with genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%